The Influence of Environment and Family on the Development of English Language Skills in Early Childhood - Ayuningtyas, Nirmala; Mardewi, Mardewi; Firdaus, Jey; Adrian, Adrian; Asdar, Asdar; Adi Nugroho, Dwi (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The study examined the influence of family and school environment on the English language skills of early childhood children at “TK Al-Falah Balombong”. The main objective of this research was to identify the factors hindering English language learning in that place, as well as to determine the extent of children’s interest to know, learn, understand, and master English. This research used a qualitative method with a descriptive approach. We found that the family and school environment at “TK Al-Falah Balombong” was not optimal in supporting English language learning. This could be seen from the language they often used at home and in their community, their local language and Indonesian, as well as the gadgets provided by their parents that did not focus on English language learning. The school also lacked competent English language teachers and adequate supporting facilities. Despite these limitations, the children showed high enthusiasm when the researchers introduced English through engaging methods such as songs and animations. To optimize this potential, interactive approaches, competent teachers, and parental support are needed to facilitate their children's English learning.